Pengetahuan, sikap dan etika batuk pada penderita tuberkulosis paru - Mohamad Ramdan; Mamat Lukman; Hesti Platini (Holistik Jurnal Kesehatan, 2020)
Knowledge, attitude and cough etiquette among patient with pulmonary tuberculosisBackground: Tuberculosis is the main cause of death. The high number of tuberculosis is due to the transmission through droplets. Cough etiquette is one of prevention behaviors of tuberculosis transmission.Purpose: To describe the knowledge, attitude and cough etiquette among patient with pulmonary tuberculosisMethod: A quantitative descriptive design with the respondent population was patient with pulmonary tuberculosis hospitalized in the Zamrud room of RSUD. Dr. Slamet Garut and the sample was selected using total sampling for one month, got of 30 respondents. The data were collected through questionnaires an observation sheets. The data were analyzed by using unnivariate analysis.Results : Showing that of 30 respondents, those who have good a knowledge were 50%, negative attitude were 63.3% and has no a cough etiquette were 56.7%.Conclusion: To be consideration to improve education delivery that is more focused on attitudes and conduct in preventing tuberculosis transmission to pulmonary tuberculosis patients and families so that they understand and apply, and can prevent tuberculosis transmission from its source.Keywords: knowledge; attitude; cough etiquette; patient; pulmonary tuberculosis Pendahuluan : Tuberkulosis penyebab kematian utama, tingginya angka kejadian tuberkulosis karena penularan melalui droplet. Etika batuk salah satu komponen perilaku pencegahan penularan tuberkulosis.Tujuan : Penelitian ini bertujuan untuk menggambarkan pengetahuan, sikap dan tindakan etika batuk pada penderita tuberkulosis.Metode: Deskriptif kuantitatif dengan populasinya semua pasien tuberkulosis paru dan pemilihan sampel menggunakan teknik total sampling untuk 1 bulan sebanyak 30 responden. Teknik pengumpulan data menggunakan kuesioner dan lembar observasi. Analisis data yang digunakan adalah distribusi frekuensi.Hasil : Menunjukan dari 30 responden, yang memiliki pengetahuan etika batuk yang baik sebesar 50%, sikap yang negatif sebesar 63.3% dan tidak beretika/tidak beradap dalam batuk sebesar 56.7%.Simpulan : Dapat dijadikan bahan pertimbangan untuk melakukan perbaikan penyampaian edukasi yang lebih berfokus pada sikap dan tindakan dalam pencegahan penularan tuberkulosis kepada penderita tuberkulosis paru dan keluarga sehingga memahami dan menerapkannya, serta dapat mencegah penularan tuberkulosis dari sumbernya.